Prospects for the use of deep brain stimulation in the treatment of Parkinson's disease in Ukraine - K.R. Kostiuk; A.O. Lisianyi; Yu.M. Medvediev; A.O. Popov; V.V. Cheburakhin; V.M. Buniakin; D.A. Tevzadze (Medičnì Perspektivi)
Aim of the study – evaluation of the results of various methods of surgical treatment of Parkinson's disease depending on the clinical manifestations and stage of the disease. The study included 566 patients with Parkinson's disease (PD), comprising 201 (35.5%) women and 365 (64.5%) men, aged 30 to 79 years (mean age 52.9±8.8 years). Radiofrequency (RF) destruction of the subcortical nuclei was performed on 522 patients: 392 underwent unilateral thalamotomy, 50 underwent bilateral thalamotomy, 36 underwent unilateral pallidotomy, 2 underwent bilateral pallidotomy, 30 underwent thalamotomy combined with contralateral pallidotomy, and 12 underwent thalamotomy combined with contralateral subthalamic nucleus (STN) destruction. Additionally, neurostimulation surgery was performed on 37 patients, and combined surgical interventions (stereotactic RF destruction and deep brain stimulation (DBS) system implantation) were performed on 7 patients. Postoperative follow-up ranged from 1 to 16 years (mean follow-up 5.2±0.9 years). One year after RF unilateral thalamotomy, tremor abolishing or significant regression was observed in 374 out of 392 patients (95.4%). Rigidity regressed in 278 out of 314 patients (88.5%) who had it before operation. Postoperative complications from unilateral thalamotomy occurred in 18 patients (4.6%). Following staged bilateral thalamotomy, tremor regression was observed in 48 out of 50 patients (96.0%) and motor fluctuations (MF) regressed in 15 out of 28 patients (53.6%). The rate of surgical complications was higher after bilateral thalamotomy (8.0%) compared to unilateral thalamotomy. After unilateral and staged bilateral pallidotomy, tremor and rigidity regression were achieved in more than two-thirds of operated patients, and levodopa-induced dyskinesias (LID) stopped in over 80% of cases. The best outcomes for alleviating motor symptoms were observed in patients who underwent DBS treatment. Staged bilateral RF ablation can be considered an alternative surgical treatment for a highly selected group of patients.